Application of a Thiadiazole‐derivative in a Tyrosinase‐based Amperometric Biosensor for Epinephrine Detection. Issue 6 (6th April 2021) - Meloni, Francesca; Spychalska, Kamila; Zając, Dorota; Pilo, Maria Itria; Zucca, Antonio; Cabaj, Joanna
Abstract: Enzyme‐based amperometric biosensors are proving to be important analytical tools in several fields such as food, environmental and, in recent years, the biomedical one. This work describes the use of 4, 7‐bis(5‐(pyridin‐2‐yl)thiophen‐2‐yl)benzo[c][1, 2, 5]thiadiazole (TBT) in the development of a tyrosinase‐based biosensor for epinephrine detection. The modifying agent was obtained as a film by electrochemical oxidation of TBT on a gold disk electrode. Electrochemical characterization and scanning electrode microscopy (SEM) images suggest the formation of a conducting film on the electrode surface. Tyrosinase from mushroom was then immobilized by a mixed technique of adsorption and cross‐linking. Glutaraldehyde was used as a coupling agent. The obtained device shows a very good linear response (0.1–50 μM) with a LoD value of 0.06 μM and a LoQ of 0.09 μM. Moreover, good selectivity towards some typical interferents (namely, ascorbic acid, tryptophan, uric acid and L‐cysteine) and satisfactory recoveries have been observed. Abstract :